Profile of scientific literacy skills of biology students - Jevi Milda Rahmawati; Atika - Anggraini; Ghaziah Kusumawati Chusjairi; Sri Rahayu Lestari; Herawati - Susilo (JPBIO (Jurnal Pendidikan Biologi), 2022)
Scientific literacy skills are very important skills to be mastered in learning activities in the 21st century. The objective of this study is to analyse the profile of scientific literacy skills of biology students of the class of 2017 at State University of Malang. This study is quantitative descriptive research. The respondents of the research were biology students in Endocrinology class,.The data were collected by conducting tests in the form of multiple-choice questions which were developed based on Test of Scientific Literacy Skills (TOSL) indicators that have been validated by material experts. The results showed that the literacy level of 25 7th biology students is still in the category of far below on five indicators with detail of the average scores, namely: identifying valid arguments with a mean value of 32; evaluating the use and misuse of information with a mean value of 16; justify inferences, predictions, and conclusions based on quantitative data with a mean value of 16; solving problems using quantitative skills including probability and statistics with a mean value of 44; understanding and interpreting basic statistics with a mean value of 24. In the other four indicators, the 25 biology students had a good level of scientific literacy, namely on indicators of understanding the design elements of research and how it affects scientific findings or conclusions with a mean value of 76; creating a graphical representation of the data with a mean value of 72; reading and interpreting graphical representations of data with a mean value of 80; and evaluating the validity of the source with a mean value of 80..